Metal-Insulator-Semiconductor Characterization by Fowler-Nordheim Carrier Tunnelling Currents Through MOS Devices - Chanana, Ravi Kumar (Transactions on Engineering and Computing Sciences, 2023)
In this research article, characterization of a Metal-Oxide-Semiconductor (MOS) device fabricated on 4H-SiC semiconductor is performed by the Fowler-Nordheim (FN) carrier tunnelling currents through the devices in accumulation and having metal gates. The technique was earlier named by the author as BOEMDET. The unknown SiO2 bandgap, the carrier effective masses in the oxide, and the conduction band (CB) and valence band (VB) offsets are determined simply from the known FN carrier tunnelling current Slope constants, the experimental bandgap of 4H-SiC, and the longitudinal electron effective mass in (0001) oriented 4H-SiC semiconductor. Three nonlinear simultaneous equations of slope constants are reduced to two with two unknowns of CB and VB offsets. Trial and error method is employed starting with a guess value of the CB offset. After several iterations, the CB and VB offsets are determined accurately that satisfy the two simultaneous equations. The unknown oxide bandgap and the carrier effective masses in thermal SiO2 are obtained further once the CB and VB offsets are known.